Cerium-doped titanium dioxide nanorod array material as well as preparation method and application thereof

By doping cerium elements and adopting hydrothermal synthesis and annealing treatment, a cerium-doped titanium dioxide nanorod array material is formed, which solves the problem of insufficient photoelectro-catalytic performance of pure titanium dioxide, and achieves efficient photoelectro-catalytic performance, which is suitable for the fields of photoelectrolytic hydrogen production such as photoelectrolytic water.

CN119898813APending Publication Date: 2025-04-29XIAMEN INST OF RARE EARTH MATERIALS
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411163074.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the field of photoelectro-catalytic, pure titanium dioxide has problems such as large band-blocking width, poor visible light absorption capacity, and easy recombination of photogenerated electrons and holes, which limits its photoelectro-catalytic performance.

Method used

By doping cerium elements, a cerium-doped titanium dioxide nanorod array material is formed. The lattice structure and electronic structure of TiO2 are adjusted by hydrothermal synthesis and annealing treatment, and new electron energy levels are introduced to inhibit the recombination of photogenerated electrons and holes.

Benefits of technology

It significantly improves the photoelectro-catalytic efficiency of titanium dioxide, improves the photocurrent density and photoelectric conversion efficiency, and is suitable for the fields of photoelectrolytic hydrogen production, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005007008700000011
    Figure HDA0005007008700000011
  • Figure HDA0005007008700000012
    Figure HDA0005007008700000012
  • Figure HDA0005007008700000021
    Figure HDA0005007008700000021
Patent Text Reader

Abstract

The invention belongs to the technical field of photoelectric catalytic materials, and particularly relates to a cerium-doped titanium dioxide nanorod array material as well as a preparation method and application thereof. Research finds that the cerium element has a large ionic radius and multivalent characteristics, and can effectively improve the photoelectrochemical properties of TiO2. The cerium doping not only can adjust the lattice structure and the electronic structure of TiO2 to expand the lattice structure, but also can introduce a new electronic energy level, adjust the electronic energy level and inhibit the compounding of photo-induced electrons and holes, so that the photocurrent density and the photoelectric conversion efficiency are remarkably improved, and the photoelectrocatalysis efficiency of titanium dioxide is improved. As a photoelectrocatalysis material, the cerium-doped titanium dioxide nanorod array material provided by the invention can be applied to the fields of photocatalysis and clean energy production, in particular to the application in hydrogen production by photoelectrolysis of water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photoelectric catalytic materials, and specifically relates to a cerium-doped titanium dioxide nanorod array material and a preparation method and application thereof. Background Art

[0002] Titanium dioxide (TiO2) is a photoelectrocatalytic material with high stability, low cost and non-toxicity, and is widely used in the fields of photoelectrochemical water splitting to produce hydrogen and photocatalytic degradation of organic pollutants. However, pure TiO2 has problems such as large bandgap, poor visible light absorption, and easy recombination of photogenerated electrons and holes, which limit its photoelectrocatalytic performance.

[0003] Scientists have found through research that by doping metal or non-metal elements, the optical and electrical properties of TiO2 can be adjusted to improve its photoelectrocatalytic performance, which has become a hot topic of research. Currently, the photoelectrocatalytic performance of titanium dioxide powder obtained by doping has been improved, but it still cannot fully meet the needs of actual production. Summary of the invention

[0004] The purpose of the present invention is to provide a cerium-doped titanium dioxide nanorod array material and a preparation method and application thereof. The cerium-doped titanium dioxide nanorod array material provided by the present invention has excellent photoelectrocatalytic performance.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The invention provides a cerium-doped titanium dioxide nanorod array material, comprising a titanium dioxide nanorod array and cerium doped in the crystal lattice of the titanium dioxide nanorod array.

[0007] Preferably, the length of the titanium dioxide nanorod array is 2.2 to 3.4 μm, and the width is 200 to 400 nm.

[0008] Preferably, the doping concentration of cerium is 0.5 to 5 mol%.

[0009] The present invention also provides a method for preparing the cerium-doped titanium dioxide nanorod array material described in the above scheme, comprising the following steps:

[0010] The conductive side of the substrate is tilted downward and placed in a hydrothermal solution for hydrothermal treatment, then taken out and heated for annealing to obtain a cerium-doped titanium dioxide nanorod array material on the substrate; the hydrothermal solution includes cerium salt, titanium butoxide, hydrochloric acid and water.

[0011] Preferably, the angle of the inclined placement (the angle with the horizontal plane) is 30 to 60°.

[0012] Preferably, the molar ratio of the cerium salt to titanium butoxide (TBOT) is 0.005-0.100:1; the volume concentration of titanium butoxide in the hydrothermal solution is 0.012%, and the volume concentration of hydrochloric acid is 20-70%.

[0013] Preferably, the temperature of the hydrothermal treatment is 160-180° C., and the insulation time is 6-8 hours.

[0014] Preferably, the starting temperature of the heating is room temperature, the end temperature is the temperature of the annealing treatment, and the heating rate is 0.5-5°C / min.

[0015] Preferably, the annealing treatment is carried out at a temperature of 450-500° C. and a holding time of 1-2 hours; and the annealing treatment is carried out in a protective atmosphere.

[0016] The present invention also provides the use of the cerium-doped titanium dioxide nanorod array material described in the above scheme or the cerium-doped titanium dioxide nanorod array material obtained by the preparation method described in the above scheme as a photoelectric catalytic material.

[0017] The present invention provides a cerium-doped titanium dioxide nanorod array material. The present invention has found that the cerium (Ce) element has a large ionic radius and multivalent characteristics, and can effectively improve the photoelectrochemical performance of TiO2. Cerium doping can not only adjust the lattice structure and electronic structure of TiO2, causing the lattice structure to expand, but also introduce new electronic energy levels, adjust the electronic energy levels, inhibit the recombination of photogenerated electrons and holes, and significantly improve the photocurrent density and photoelectric conversion efficiency, thereby improving the photoelectrocatalytic efficiency of titanium dioxide.

[0018] The present invention also provides a method for preparing the cerium-doped titanium dioxide nanorod array material of the above scheme. The present invention utilizes a hydrothermal synthesis method and combines annealing treatment to obtain a cerium-doped titanium dioxide nanorod array material with excellent photoelectrochemical performance and high photoelectrocatalytic efficiency.

[0019] The present invention also provides the use of the cerium-doped titanium dioxide nanorod array material described in the above scheme or the cerium-doped titanium dioxide nanorod array material obtained by the preparation method described in the above scheme as a photoelectrocatalytic material. The cerium-doped titanium dioxide nanorod array material provided by the present invention can be applied to the fields of photocatalysis and clean energy production as a photoelectrocatalytic material, especially in the application of photoelectrolytic water hydrogen production, has excellent photoelectrolytic water hydrogen production performance, has broad application prospects, and is expected to play an important role in the fields of photocatalysis and clean energy production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 This is the X-ray diffraction (XRD) pattern of the cerium-doped titanium dioxide nanorod array material;

[0022] Figure 2 is a scanning electron microscope (SEM) image of a cerium-doped titanium dioxide nanorod array material; wherein, Figure 2 (a) is a scanning electron microscope image of R. Figure 2 (b) is a scanning electron microscope image of CR5. Figure 2 (c) is a scanning electron microscope image of CR10;

[0023] Figure 3 is an X-ray photoelectron spectroscopy (XPS) spectrum of cerium-doped titanium dioxide nanorod array material; wherein, Figure 3 (a) is the full spectrum. Figure 3 (b) is Ti, Figure 3 Where (c) is O, Figure 3 Middle (d) is Ce;

[0024] Figure 4 The results of the hydrogen production efficiency test of cerium-doped titanium dioxide nanorod array materials are shown in Figure 2. Figure 4 (a) is the hydrogen production in 10 hours. Figure 4 (b) is the hydrogen production rate;

[0025] Figure 5 The results of the photoelectric conversion efficiency and stability test of cerium-doped titanium dioxide nanorod array materials are shown in Figure 2. Figure 5 The left side is the LSV curve under the chopping experiment, and the right side is the photoelectric conversion efficiency curve;

[0026] Figure 6 The incident photon-current efficiency (IPCE) test results of cerium-doped titanium dioxide nanorod array materials; wherein, Figure 6 (a) is the wavelength-photocurrent spectrum in noise mode. Figure 6 (b) is the wavelength-photocurrent spectrum under different bias voltages. Figure 6 (c) is the IPCE spectrum in noise mode. Figure 6 (d) is the IPCE spectra under different bias voltages;

[0027] Figure 7is the band gap and Mott-Schottky (MS) diagram of the cerium-doped titanium dioxide nanorod array material; wherein, Figure 7 (a) is the band gap calculated by IPCE in ECN mode (IPCE%×hν) 1 / 2 vs.hν graph, Figure 7 (b) is the MS curve diagram;

[0028] Figure 8 The electrochemical impedance spectroscopy (EIS) of cerium-doped titanium dioxide nanorod array material is shown in FIG. Figure 8 (a) is the electrochemical impedance spectroscopy diagram. Figure 8 (b) is a local enlarged view;

[0029] Fig. 9 The band gap diagram and photocatalytic mechanism diagram of cerium-doped titanium dioxide nanorod array materials; Fig. 9 (a) is the band gap diagram, Fig. 9 (b) is a schematic diagram of the photocatalytic mechanism;

[0030] Fig.10 Process flow chart for cerium-doped titanium dioxide nanorod array material. DETAILED DESCRIPTION

[0031] The invention provides a cerium-doped titanium dioxide nanorod array material, comprising a titanium dioxide nanorod array and cerium doped in the crystal lattice of the titanium dioxide nanorod array.

[0032] In the present invention, the length of the titanium dioxide nanorod array is preferably 2.2 to 3.4 μm, more preferably 2.5 to 3.0 μm, and further preferably 2.7 to 2.8 μm, and the width is preferably 200 to 400 nm, more preferably 250 to 350 nm, and further preferably 300 nm.

[0033] In the present invention, the titanium dioxide in the titanium dioxide nanorod array is preferably rutile phase titanium dioxide.

[0034] In the present invention, the doping concentration of cerium is preferably 0.5 to 5 mol %, more preferably 1 to 4 mol %, and further preferably 2 to 3 mol %.

[0035] The present invention also provides a method for preparing the cerium-doped titanium dioxide nanorod array material described in the above scheme, comprising the following steps:

[0036] The conductive side of the substrate is tilted downward and placed in a hydrothermal solution for hydrothermal treatment, then taken out and heated for annealing to obtain a cerium-doped titanium dioxide nanorod array material on the substrate; the hydrothermal solution includes cerium salt, titanium butoxide, hydrochloric acid and water.

[0037] The present invention places the conductive side of the substrate in a hydrothermal solution with the substrate tilted downward. In the present invention, the substrate is preferably a FTO glass sheet; the substrate is preferably pretreated before use; the pretreatment is preferably: the substrate is sequentially cleaned with acetone, cleaned with ethanol, cleaned with ultrapure water, and dried (referred to as the first drying).

[0038] In the present invention, the acetone cleaning, ethanol cleaning and ultrapure water cleaning are independently preferably ultrasonic cleaning; the frequency of the ultrasonic cleaning is preferably 35 to 50 kHz, more preferably 40 to 45 kHz, the power is preferably 100 to 500 W, more preferably 300 to 400 W, and the time is preferably 5 to 20 min, more preferably 10 min.

[0039] In the present invention, the first drying temperature is preferably 40-70° C., more preferably 60° C., and the heat preservation time is preferably 30-60 min, more preferably 40 min.

[0040] In the present invention, the angle of the inclined placement (the angle with the horizontal plane) is preferably 30° to 60°, more preferably 45°; the inclined placement is preferably placed close to the tube wall.

[0041] In the present invention, the molar ratio of the cerium salt to titanium butoxide (TBOT) is preferably 0.005-0.100:1, more preferably 0.01-0.10:1, further preferably 0.02-0.10:1, and further preferably 0.04-0.05:1; the volume concentration of titanium butoxide in the hydrothermal solution is preferably 0.012%, and the volume concentration of hydrochloric acid is preferably 20-70%, more preferably 30-50%, and further preferably 50%.

[0042] In the present invention, the cerium salt is preferably cerium nitrate hexahydrate (Ce(NO3)3·6H2O); and the water in the hydrothermal solution is preferably ultrapure water.

[0043] In the present invention, the method for preparing the hydrothermal solution is preferably: first mixing water and concentrated hydrochloric acid to obtain a premixed solution, then second mixing the premixed solution and titanium butoxide solution to obtain a mixture, and then third mixing the mixture and cerium salt.

[0044] In the present invention, the first mixing is preferably stirring mixing; the first mixing time is preferably 10 to 30 minutes, more preferably 15 minutes; the second mixing is preferably stirring mixing; the second mixing time is preferably 10 to 40 minutes, more preferably 30 minutes. In the present invention, the hydrothermal solution is stirred until it is clear through the second mixing.

[0045] After tilting, the present invention performs hydrothermal treatment in a hydrothermal solution and then takes it out and raises the temperature for annealing treatment, thereby obtaining a cerium-doped titanium dioxide nanorod array material on the substrate. In the present invention, the hydrothermal treatment equipment is preferably an autoclave; the lining of the autoclave is preferably Teflon; the temperature of the hydrothermal treatment is preferably 160 to 180°C, more preferably 165 to 175°C, and further preferably 170°C, and the insulation time is preferably 6 to 8 hours, more preferably 6.5 to 7.5 hours, and further preferably 7 hours.

[0046] In the present invention, the hydrothermal treatment preferably further includes naturally cooling the reaction system.

[0047] In the present invention, after the natural cooling, the process preferably further comprises taking out the obtained product from the reaction device, washing it and then drying it (referred to as the second drying).

[0048] In the present invention, the cleaning preferably comprises sequentially performing ethanol cleaning and water cleaning.

[0049] In the present invention, the second drying temperature is preferably 40° C. to 70° C., more preferably 60° C., and the heat preservation time is preferably 30 to 60 min, more preferably 40 min.

[0050] In the present invention, the starting temperature of the heating is preferably room temperature, the end temperature is preferably the temperature of the annealing treatment, and the heating rate is preferably 0.5 to 5° C. / min, more preferably 1° C. / min.

[0051] In the present invention, the annealing temperature is preferably 450-500°C, more preferably 460-490°C, further preferably 470-480°C, and the holding time is preferably 1-2h, more preferably 1.5h; the annealing is preferably carried out in a protective atmosphere; the protective atmosphere is preferably argon.

[0052] The present invention utilizes a hydrothermal synthesis method and combines annealing treatment to obtain a cerium-doped titanium dioxide nanorod array material with excellent photoelectrochemical performance and high photoelectrocatalytic efficiency. The specific process flow is as follows: Fig.10 shown.

[0053] The present invention also provides the use of the cerium-doped titanium dioxide nanorod array material described in the above scheme or the cerium-doped titanium dioxide nanorod array material obtained by the preparation method described in the above scheme as a photoelectric catalytic material.

[0054] The cerium-doped titanium dioxide nanorod array material provided by the present invention can be used as a photoelectrocatalytic material in the fields of photocatalysis and clean energy production, especially in the application of photoelectrolytic water splitting to produce hydrogen. It has excellent photoelectrolytic water splitting to produce hydrogen performance and has broad application prospects, and is expected to play an important role in the fields of photocatalysis and clean energy production.

[0055] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.

[0056] Comparative Example 1

[0057] Undoped Titanium Dioxide Materials

[0058] (1) The FTO glass sheet was ultrasonically cleaned with acetone, ethanol and ultrapure water for 10 minutes each, and dried for later use.

[0059] (2) 15 mL of ultrapure water and 15 mL of concentrated hydrochloric acid (mass concentration of 37%) were mixed and stirred for 15 min, 0.36 mL of titanium butoxide solution was added, and stirring was continued for 30 min to obtain a clear hydrothermal solution.

[0060] (3) The hydrothermal solution was added into a Teflon-lined autoclave, and a clean FTO glass sheet was placed with the conductive side facing downward at an angle of 45° close to the tube wall, and hydrothermally treated at 170° C. for 6 h, and naturally cooled to obtain a photoanode.

[0061] (4) The photoanode was taken out, rinsed with ethanol and water respectively, dried, and heated from room temperature to 450° C. at a heating rate of 1° C. / min, and kept warm for 1 hour to obtain an undoped titanium dioxide material, which was recorded as photoanode R.

[0062] Example 1

[0063] Preparation of Ce-doped Titanium Dioxide Nanorod Arrays

[0064] The preparation method of this embodiment is the same as that of Comparative Example 1, except that step (2) is:

[0065] 15 mL of ultrapure water and 15 mL of concentrated hydrochloric acid (mass concentration of 37%) were mixed and stirred for 15 minutes, 0.36 mL of titanium butoxide solution was added, and stirring was continued for 30 minutes to obtain a mixed solution, and then 21.7 mg (equivalent to a doping concentration of 5%) of cerium nitrate hexahydrate was added to the mixed solution to obtain a clear hydrothermal solution.

[0066] The remaining steps are the same, and finally a cerium-doped titanium dioxide nanorod array material is obtained, which is denoted as photoanode CR5.

[0067] Example 2

[0068] The preparation method of this embodiment is the same as that of embodiment 1, the only difference being step (2):

[0069] 15 mL of ultrapure water and 15 mL of concentrated hydrochloric acid (mass concentration of 37%) were mixed and stirred for 15 minutes, 0.36 mL of titanium butoxide solution was added, and stirring was continued for 30 minutes to obtain a mixed solution, and then 43.4 mg (equivalent to a doping concentration of 10%) of cerium nitrate hexahydrate was added to the mixed solution to obtain a clear hydrothermal solution.

[0070] The remaining steps are the same, and finally a cerium-doped titanium dioxide nanorod array material is obtained, which is denoted as photoanode CR10.

[0071] Test Example 1 Morphology and Composition Characterization

[0072] 1. The crystal structure and phase of the material of Example 1 were analyzed by X-ray diffraction (Miniflex 600 system, Rigaku, Tokyo, Japan) with a scanning range of 20° to 80°, a scanning rate of 5° / min, and Cu Kα radiation (λ = 0.15406 nm). The results are as follows: Figure 1 As shown. Figure 1 The X-ray diffraction patterns show that with the increase of Ce doping concentration, the diffraction peak of the rutile phase (110) shifts to a lower angle.

[0073] 2. The morphology of the materials in Examples 1 and 2 was characterized using a field emission scanning electron microscope (Apreo SLoVac, Thermo Fisher, Waltham, MA, USA) to observe the morphology of the cerium-doped titanium dioxide nanorod arrays. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the TiO2 photoanode and the Ce-doped TiO2 photoanode prepared in the present invention have a very neat rod-like arrangement structure.

[0074] 3. X-ray photoelectron spectroscopy (Thermo Scientific K-Alpha system, Waltham, MA, USA) was used to analyze the surface chemical properties of the material in Example 1, including chemical species, state and concentration. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the doping concentration of Ce ions is very low and the characteristic peak of Ce element is very weak.

[0075] 4. The materials of Examples 1 and 2 were analyzed using a high-resolution transmission electron microscope (TECNAI F30, Philips FEI, Eindhoven, Netherlands) to obtain information on lattice fringes and crystallinity.

[0076] The test results show that the cerium-doped titanium dioxide nanorod array materials of Examples 1 and 2 have high crystallinity, uniformly arranged lattice fringes, and a specific orientation of the (110) crystal plane.

[0077] Test Example 2 Photoelectrolysis of water to produce hydrogen

[0078] (1) Photoelectrochemical water splitting was tested in a Labsolar-6A photochemical reactor. The electrolyte was 60 mL of 0.1 M Na2SO4 solution without sacrificial agent.

[0079] (2) Use FL9790 gas chromatograph to detect and analyze the generated gas every 30 minutes.

[0080] (3) Test conditions: AM 1.5G light source, light intensity 100mW / cm 2 The immersion area of ​​the working electrode in the electrolyte is 1×1 cm 2 , the test results are as follows Figure 4 shown.

[0081] according to Figure 4 It can be seen that the hydrogen production efficiency of the material in Example 1 reaches 37.03 μmol·cm -2 ·h -1 , which is significantly higher than the undoped titanium dioxide photoanode in Comparative Example 1.

[0082] Test Example 3 Photoelectrochemical Performance Test

[0083] (1) The photoelectrochemical performance was tested in 0.1 M Na2SO4 electrolyte using a standard three-electrode system, with the working electrode being the photoanode, the reference electrode being the saturated Ag / AgCl electrode, and the counter electrode being a Pt metal sheet (1×1 cm 2 ).

[0084] (2) Using the SquidstatPlus electrochemical workstation, a bias voltage of 1.23 V (relative to RHE) was applied to test the photocurrent density and photoelectric conversion efficiency. The results are as follows: Figure 5 shown.

[0085] according to Figure 5 It can be seen that the photocurrent density of the cerium-doped titanium dioxide nanorod array material in Example 1 reached 1.98 mA / cm 2 ; According to the photoelectrochemical properties of the materials in Comparative Example 1 and Example 1, it can be seen that cerium doping significantly improves the photocurrent density and photoelectric conversion efficiency of the materials.

[0086] Test Example 4 Photocurrent IPCE test

[0087] (1) The photocurrent IPCE curve is used to study the light absorption range of the photoanode.

[0088] (2) The IPCE1000 test system and the CS350H electrochemical workstation were used to perform constant potential wavelength scanning tests. The test conditions were: wavelength step size of 1 nm, wavelength range of 300-600 nm, and effective light area of ​​1 × 1 cm 2 , the results are as follows Figures 6-7 and Fig. 9 shown.

[0089] according to Figure 6 It can be seen that the materials of Examples 1 and 2 exhibit excellent light absorption under long-term illumination.

[0090] according to Figure 7 It can be seen that Figure 7 The normalized IPCE curve in a provides the band gap values ​​of Ce-TiO2 photoanode, where the band gaps of R, CR5 and CR10 are 2.87 eV, 2.84 eV and 2.86 eV, respectively. This indicates that the doping of Ce ions slightly reduces the band gap of TiO2, which may be due to the introduction of Ce ions causing slight lattice distortion in TiO2, thus affecting its electronic structure; Figure 7 (b) shows that the flat band potentials of the R, CR5, and CR10 photoanodes are −0.06 V, −0.32 V, and −0.21 V (vs. RHE), respectively.

[0091] Depend on Figure 7 Data obtained Fig. 9 ,according to Fig. 9 It can be seen that compared with the original TiO2 photoanode, the Ce-TiO2 photoanode has a more negative flat band potential, indicating that its electron reduction ability is enhanced, which is beneficial to the catalytic hydrogen evolution reaction.

[0092] Test Example 5

[0093] (1) The electrochemical impedance spectroscopy (EIS) performance was tested in 0.1 M Na2SO4 electrolyte using a standard three-electrode system. The working electrode was a cerium-doped titanium dioxide photoanode, the reference electrode was a saturated Ag / AgCl electrode, and the counter electrode was a Pt metal sheet (1 × 1 cm 2 ).

[0094] (2) In EIS experiments, the test frequency is usually 10mHz to 100kHz. In actual EIS experiments, the curve of the Nyquist plot tends to show a distorted semicircular or straight line shape, because the shape of the curve may be affected by the intrinsic or electrochemical properties of the electrode, electrolyte and experimental conditions. Figure 8 shown.

[0095] according to Figure 8It can be seen that the arc radius of the EIS curves of R, CR5 and CR10 photoanodes is smaller than that of the R photoanode. The smaller the arc radius, the smaller the charge transfer resistance at the interface between the electrode and the electrolyte, indicating that the doping of Ce element improves the photogenerated charge transfer performance of TiO2 nanorods.

[0096] It can be seen from the above examples that the cerium-doped titanium dioxide nanorod array material provided by the present invention has excellent photoelectrocatalytic performance and can be used for photoelectrolytic water splitting to produce hydrogen.

[0097] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A cerium-doped titanium dioxide nanorod array material, characterized in that: The invention comprises a titanium dioxide nanorod array and cerium doped in the crystal lattice of the titanium dioxide nanorod array.

2. The cerium-doped titanium dioxide nanorod array material according to claim 1, characterized in that: The length of the titanium dioxide nanorod array is 2.2-3.4 μm, and the width is 200-400 nm.

3. The cerium-doped titanium dioxide nanorod array material according to claim 1 or 2, characterized in that: The doping concentration of cerium is 0.5 to 5 mol%.

4. The method for preparing the cerium-doped titanium dioxide nanorod array material according to any one of claims 1 to 3, characterized in that: The following steps are involved: The conductive side of the substrate is tilted downward and placed in a hydrothermal solution for hydrothermal treatment, then taken out and heated for annealing to obtain a cerium-doped titanium dioxide nanorod array material on the substrate; the hydrothermal solution includes cerium salt, titanium butoxide, hydrochloric acid and water.

5. The preparation method according to claim 4, characterized in that: The angle of the inclined placement is 30 to 60 degrees.

6. The preparation method according to claim 4 or 5, characterized in that: The molar ratio of the cerium salt to titanium butoxide is 0.005 to 0.100:1; The volume concentration of titanium butanol in the hydrothermal solution is 0.012%, and the volume concentration of hydrochloric acid is 20-70%.

7. The preparation method according to claim 4, characterized in that: The temperature of the hydrothermal treatment is 160-180° C., and the insulation time is 6-8 hours.

8. The preparation method according to claim 4 or 7, characterized in that: The starting temperature of the heating is room temperature, the end temperature is the temperature of the annealing treatment, and the heating rate is 0.5-5°C / min.

9. The preparation method according to claim 4, characterized in that: The annealing treatment is carried out at a temperature of 450-500° C. and a heat preservation time of 1-2 hours; the annealing treatment is carried out in a protective atmosphere.

10. Use of the cerium-doped titanium dioxide nanorod array material according to any one of claims 1 to 3 or the cerium-doped titanium dioxide nanorod array material obtained by the preparation method according to any one of claims 4 to 9 as a photoelectrocatalytic material.

Citation Information

Cited By

  • Water-based lanthanum-doped titanium dioxide reflective heat-insulation coating and preparation method thereof

    CN122188451A